THEIR LAW IN OUR HANDS – THE APPLICATION OF ENGLISH LAW ACT 1993 (SINGAPORE): ARE THERE LESSONS FOR THE CIVIL LAW ACT OF 1956 (MALAYSIA)? - CHAN SEK KEONG (Journal of Malaysian and Comparative Law, 2025)
The 13th Tun Suffian Memorial Lecture 2024 delivered at the Faculty of Law, Universiti Malaya, Kuala Lumpur, 50603, Malaysia on 10 October 2024.